Decrease of Free Fatty Acid Levels in Cooking Oil Using Sugar Cane - Nasukwad Nasukwad; Alwi Ahmad Sulthon (Journal of Natural Sciences and Mathematics Research, 2019)
Edible Oil has a fairly high economic value. Cooking oil is generally used for cooking. With the condition of oil prices increasing so many times it is necessary to recycle again so as not to pollute the environment. Used cooking oil has a lot of high free fatty acid content, so it is necessary to reduce fatty acids by using absorbent ingredients. Sugarcane bagasse can be used as a purification ingredient of used cooking oil by soaking. This study aims to determine the level of soaking bagasse against free fatty acid numbers. Variable immersion for 0 hours, 24 hours, 48 hours, and 72 hours. The results of the percentage of Free Fatty Acid (ALB) levels after done, soaking time for 0 hours is 0.36%, 24 hours is 0.34%, 48 hours is 0.33%, and 72 hours is 0.29%.©2019 JNSMR UIN Walisongo. All rights reserved.